VALIDATION OF A HEATING SYSTEM IN THE FARROWING HOUSE USING A CFD APPROACH - Damasceno,Flávio A. (2018)
ABSTRACT The current heating system for piglets in the farrowing usually uses incandescent lamps and, in some cases, heated floors with electric resistances, which in most cases generates a high energy cost. Thus, the implantation of systems that use renewable energies in the heating of piglets can allow the thermal comfort of the animals without reducing the productive development. The objective of this research was to evaluate a computer model in Computational Fluid Dynamics (CFD), which predicts surface temperature in the heating system of a farrowing house. The study was conducted during the summer season on the swine sector of Federal University of Lavras, Brazil. For this study, a prototype solar heater using alternative materials (ASWH) was developed and compared with a conventional solar water heater (CSWH). Two floors were built of cement to test both heating systems and four thermocouple sensors (K type) with digital display were used in each system to test and evaluate the heating efficiency. Based on the results, the average surface temperature in the ASWH and the CSWH treatments was 27.9 ± 2.6 °C and 27.1 ± 1.9 °C, respectively. Therefore, the experimental data showed no significant differences from the data obtained by the model, enabling the conclusion that it is suitable for predicting the thermal conditions of this type of heating system and could be used in swine factories to predict energy consumption. Thus, this computational model can be used as a useful tool for the design and selection of heating systems used in swine maternity systems.